Spatial and Temporal Variation in Otolith Chemistry of Juvenile Atlantic Menhaden in the Chesapeake Bay. Issue 4 (2nd July 2014) - Schaffler, Jason J.; Miller, Thomas J.; Jones, Cynthia M.
Abstract: The Atlantic Menhaden Brevoortia tyrannus is an important component of the estuarine and nearshore fish assemblages in the mid‐Atlantic region. It serves as a forage species for many piscivorous fish, birds, and marine mammals as well as being subject to an important commercial fishery. Currently there is concern over low standing stocks and recruitment, yet few studies have addressed those concerns. We evaluated the effectiveness of using an otolith chemistry approach to identify juvenile menhaden nursery areas throughout the Chesapeake Bay over 2 years. If successful, an otolith chemistry approach is capable of addressing a number of hypotheses regarding the source and fate of recruits in a stock. We found multiple unique otolith chemistry signatures in menhaden collected in the Chesapeake Bay. Overall correct classification was 85% for the 2005 cohort and 95% for the 2006 cohort. The ratios of most trace element: Ca and stable isotope ratios were different among areas. In addition to spatial differences, both seasonal and annual temporal variation was present in the otolith chemistry. However, a discriminant function that included temporal variation resulted in reduced prediction accuracy (overall errors increased 7–10%). We found that our classification function, which was developed for multiple cohorts, can successfully predict group membership. We recommend additional evaluation of this strategy because of its potential application to data‐poor stocks. Our data show that juvenile menhaden in the Chesapeake Bay can be reliably discriminated based on otolith chemistry signatures and that this approach can be used to critically evaluate the nursery contributions of the bay to the coastal adult stock of menhaden. Received July 11, 2013; accepted January 21, 2014